Privacy and Security in Big Data, Categories, Issues, and Proposed Solutions - Younus AbdulKareem Mohammed (Journal of Madenat Alelem University College, 2022)
In recent years, one of the most contentious issues has been "big data." Unstructured and semi-structured data may be found in many locations, including web servers, mobile devices, and social media sites, for many organizations and enterprises, the security and privacy of large data are becoming more critical, and the increased usage of big data puts data security and privacy at odds. Large-scale data sharing raises new privacy and security issues. Big data doesn’t work with traditional methods or techniques. Analyzing large amounts of data encourages the collection and long-term storage of more complete and durable data. By combining private data with other private data, it is possible to reveal the personal information of its customers more easily. The sharing of massive data opens the door to new problems. It necessitates the use of high-tech methods and tools because they create so many data security issues. As part of our review of Big Data privacy and security the most recent methods, mechanisms, and solutions for protecting data-intensive systems were discussed. we looked at the most important terms to define and classify, in this paper, big data security and privacy researchers will benefit from this review because it identifies key trends and general terms, as well as current privacy and security concerns. And we also highlighted common solutions to these problems included.